2012
DOI: 10.1177/002205741219200105
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Novels: What Elementary Teachers Think about Their Instructional Value

Abstract: Survey methods were employed to learn more about teachers’ attitudes toward graphic novels and how graphic novels are used in their classrooms. Questions explored participants’ attitudes and actual classroom use. The survey research sought to determine if teachers are open to using graphic novels and the extent of their willingness to do so. Though teachers report willingness to use graphic novels and other graphica, they are limited in their attempts to do so by lack of instructional models, lack of graphic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 8 publications
(9 reference statements)
1
31
0
Order By: Relevance
“…An abundance of quality graphic novels, comic books, magazines, and digital texts are now available to share with students, and these alternative texts are often highly engaging, particularly for reluctant readers (Schwarz, ). Many graphic novels, for example, have merit in terms of both literary quality and interest level, yet they are often overlooked in the elementary classroom library (Lapp, Wolsey, Fisher, & Frey, ). Examples of excellent graphic novels include Rapunzel's Revenge by Shannon Hale and Dean Hale, Smile by Raina Telgemeier, and El Deafo by Cece Bell.…”
Section: Four Research‐based Principles Of Interest and Readingmentioning
confidence: 99%
“…An abundance of quality graphic novels, comic books, magazines, and digital texts are now available to share with students, and these alternative texts are often highly engaging, particularly for reluctant readers (Schwarz, ). Many graphic novels, for example, have merit in terms of both literary quality and interest level, yet they are often overlooked in the elementary classroom library (Lapp, Wolsey, Fisher, & Frey, ). Examples of excellent graphic novels include Rapunzel's Revenge by Shannon Hale and Dean Hale, Smile by Raina Telgemeier, and El Deafo by Cece Bell.…”
Section: Four Research‐based Principles Of Interest and Readingmentioning
confidence: 99%
“…Much of the scholarship around using graphic novels in the classroom has ignored the design elements of graphic novels and the scaffolds that are likely needed to ensure that students know how to read the multiple cuing systems (Chase, Son, & Steiner, ; Connors, ; Pantaleo, ). One survey study of elementary teachers found that the respondents considered themselves novice graphic novel readers at a loss as to how to instruct students in selecting, evaluating, and reading graphic novels (Lapp, Wolsey, Fisher, & Frey, ). Connors suggested that the reasons for the limited understanding may be a result of the lack of teacher preparation and professional development directly related to multimodal texts:
Nor is visual literacy the subject of professional development programming for in‐service teachers with any degree of frequency.
…”
Section: Graphic Novels As Multimodal Textmentioning
confidence: 99%
“…Access to resources and digital tools continues to present obstacles in many schools (Rowsell, Morrell, & Alvermann, 2017). Teachers who embrace multimodal texts may be hampered in teaching them effectively because of limited knowledge of the genre or instructional approaches (Lapp, Wolsey, Fisher, & Frey, 2011), or criticism from parents, administrators, or even students (Hansen, 2012). One type of multimodal text, graphic novels, has been questioned by students as not legitimate for "real" reading (Moeller, 2016).…”
mentioning
confidence: 99%